2021
DOI: 10.3390/brainsci11030373
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Parkinson’s Disease: iPSCs towards Better Understanding of Human Pathology

Abstract: Parkinson’s Disease (PD) is a chronic neurodegenerative disorder characterized by motor and non-motor symptoms, among which are bradykinesia, rigidity, tremor as well as mental symptoms such as dementia. The underlying cause of Parkinson disease is degeneration of dopaminergic neurons. It has been challenging to develop an efficient animal model to accurately represent the complex phenotypes found with PD. However, it has become possible to recapitulate the myriad of phenotypes underlying the PD pathology by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 197 publications
1
20
0
Order By: Relevance
“…However, this increase was not significant compared to DA neuronal culture from a healthy donor. The absence of LB-like α-syn accumulation is a general limitation of currently available cellular models of PD [12]. Importantly, we observed punctated accumulation of pathological α-syn (pS129 positive) next to the nucleus of cells derived from fPD lines, spatially and morphologically resembling LBs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, this increase was not significant compared to DA neuronal culture from a healthy donor. The absence of LB-like α-syn accumulation is a general limitation of currently available cellular models of PD [12]. Importantly, we observed punctated accumulation of pathological α-syn (pS129 positive) next to the nucleus of cells derived from fPD lines, spatially and morphologically resembling LBs.…”
Section: Discussionmentioning
confidence: 63%
“…DA neuronal cultures derived from fPD patients manifested different aspects of PD pathology (reviewed by Sahar Avazzadeh et al, 2021 (ref. [12])). Although α-syn accumulation in fPD-iPSC-derived DA neurons has been reported in multiple studies, the formation of LB-like structures in these cells has not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…α-synuclein is encoded by the SNCA gene which is found on chromosome 4 (4q21. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and mutations of this gene show an autosomal dominant pattern of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…This type of approach is commonly known as 'disease in a dish' modelling (12) (Figure 1). This methodology has the advantage of maintaining the patient's complete genetic background and allows the impact of certain key mutations on pathophysiology to be studied, allowing the characterization of key cellular mutation-based phenotypes in complex diseases such as Parkinson's disease (13). Dopaminergic (DA) neurons are the main cell type used to study neurodegeneration in Parkinson's disease using several different protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation